PROBLEMS OF DEVELOPMENT OF PROJECTS OF THE PIPELINE SERVICE IN THE CASPIAN REGION - D. Kuramshin (Вестник университета)
The present stage of development of energy cooperation in the Caspian region is characterized by strengthening of contradictions between the countries. In the article tendencies of development of new projects of a pipeline service in the region are defined. Competitive opportunities of Russia in development of hydrocarbonic resources of the Caspian Sea are estimated.